STUDI KOMPARASI KUAT TEKAN BETON DENGAN PENAMBAHAN SEKAMPADI DAN ABU SEKAM - Yunita; Toar Pangkey; Tendly Maki; Tendly Maki, (Sustainable Construction (SUSCON), 2024)
Padi seals are waste from the grinding of padi that is not used effectively by society. Padi seeds contain 93% slika, almost the same as the slika content of microsilica, which makes it a pozzalan. Besides, peaches also contain pozzalani. Melted ashes come from the remains of brick burning, and these wastes are less used for any purpose. The reactive Si02 produced from damp ashes at 600–700 °C will be used as a material to make artificial pozzolan. Waste from grinding padi that is not used effectively by society. Therefore, the researchers wanted to use the waste of clay and clay as additives to the mixture of concrete test objects in the form of a cylinder test to measure concrete pressure strength. In this study, I used variations of 6%, 12%, and 18%, respectively. In this research, experimental methods were used to make a test object and then perform a strong pressure test by looking at the resulting data. The results of the calculation showed that a variation of 6% of the ashes had a strong pressure of an average of 27,0953 Mpa, a variance of 12% had an average value of 21,4683 MPa, and a variation of 18% of a ashes has an average values of 17,952 Mpa. A strong pressure of concrete without adding material averaged 24,985 MPa.